2019
DOI: 10.1101/758540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic base substitution patterns in diverse species reveal links to cancer and metabolism

Abstract: 1Mutations in genomic DNA are the starting material for evolution by natural 2 selection. Analyses of large-scale sequencing data have revealed that mu-3 tagenic processes often create distinctive patterns of base substitutions, 4 called mutational signatures. In this work, we analyzed the base substitu-5 tion patterns within mutational data from a large number of strains or indi-6 viduals among seven model species (totalling >784 million mutations), as 7 well as single nucleotide polymorphisms (SNPs) in 41 sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…The genomes mutagenized by either small aldehyde were compared to control genomes that were not treated by either. Analysis of the untreated control genomes revealed a mutational pattern where C/G > T/A and T/A > C/G transitions outnumbered the four types of transversions (namely C/G > A/T, C/G > G/C, T/A > A/T, and T/A > G/C, see Figure 2a), similar to what we had observed previously (53). By comparison, formaldehyde and acetaldehyde treatment both caused a relative increase of C/G > A/T transversions (see Figure 2b and 2c).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The genomes mutagenized by either small aldehyde were compared to control genomes that were not treated by either. Analysis of the untreated control genomes revealed a mutational pattern where C/G > T/A and T/A > C/G transitions outnumbered the four types of transversions (namely C/G > A/T, C/G > G/C, T/A > A/T, and T/A > G/C, see Figure 2a), similar to what we had observed previously (53). By comparison, formaldehyde and acetaldehyde treatment both caused a relative increase of C/G > A/T transversions (see Figure 2b and 2c).…”
Section: Resultssupporting
confidence: 87%
“…We previously studied an SBS5-like mutational pattern in yeast and showed that similar patterns are widely conserved in many species. Moreover, the SBS5-like pattern is due to error-prone translesion DNA synthesis in the absence of added mutagens and increases with increasing sugar metabolism (38). An SBS40-like mutational pattern would require a separate explanation, which would be the addition of exogenous formaldehyde to our experimental system.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we explored the mechanisms that contribute to a very common form of mutagenesis whose overall pattern resembles SBS signature 5 from COSMIC. Analogs of these similar mutational patterns are found in many biological systems (34). Given the ubiquitous nature of this set of related mutational patterns, we reasoned that the etiology is likely to be related to some endogenous process or agent that is well conserved, and that many biological systems are exposed to routinely.…”
Section: Discussionsupporting
confidence: 62%
“…Turning our attention to a less obvious candidate etiology, we eventually found that changing the carbon source metabolism of yeast cells did have large effects on SBS5-like mutagenesis. That set of results implicated the completion of glycolysis as an important requisite process for observing the SBS5-like mutagenesis (34). In this study, we ran additional experiments which consolidated and reaffirmed the results showing that glucose concentration is an important determinant of mutagenesis, while mitochondrial function is dispensable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation